Vegetable Production in Changing Climate Scenario: Challenges and Mitigation - Prabal Thakur; ML Bhardwaj; Ramesh K Bhardwaj; Ashok K Thakur; Amit Vikram (International Journal of Economic Plants)
The major climate changes viz., increase in temperature, enhanced evapo-transpiration, uncertainty of precipitation and seasonal variability, affect vegetable production technologies particularly choice of variety, sowing time, plant protection, nutrient and water management. Reduced GHG emission may help in minimizing the changes and their effects, but this reduction should not be expected from poor and developing counties at the expense of development. The developing countries with justified financial support may mitigate and lower the emissions by effective technology transfer, investment in eco–friendly infrastructure, encouragement of biodiversity conservation and good practices. Germplasm of the major vegetable crops tolerant to high temperatures, flooding and drought has been identified and advanced breeding lines are required to be developed. Furthermore, nurient-use efficient germplasm also need to be identified. In addition, development of water-use efficient production systems is key tool to mitigate the effects of hot and dry conditions. Not all the effects are negative. Agriculture emits and traps green house gases. The beneficial effects of CO2 enhancement on crop growth need to be exploited. Farm practices can be modified to reduce emissions and to sequester the green house gases. We need to emphasize low external input agriculture particularly organic farming. Such low or no fertilizer farming shall be subsidized to the tune of social benefits of emission reduction. In global scenario, low GHG emissions in developing countries have made it possible to sustain the high pattern of energy consumption by the industrialized countries for decades and shall continue. People in high-income countries with higher carbon emission rate can buy organic products to promote such practices. The pricing of organic vegetable should include external benefits of reducing GHG emissions so that high-income people pay for their higher emission of GHG.